Viral Mimicry as a Design Template for Nucleic Acid Nanocarriers - de la Fuente, Ina F.; Sawant, Shraddha S.; Tolentino, Mark Q.; Corrigan, Patrick M.; Rouge, Jessica L. (Frontiers in Chemistry, 2021)
Therapeutic nucleic acids hold immense potential in combating undruggable, gene-based diseases owing to their high programmability and relative ease of synthesis. While the delivery of this class of therapeutics has successfully entered the clinical setting, extrahepatic targeting and endosomal escape efficiency remain as major roadblocks. On the other hand, viruses serve as natural carriers of nucleic acids and have acquired a plethora of structures and mechanisms that confer remarkable transfection efficiency. Thus, understanding the structure and mechanism of viruses can guide the design of synthetic nucleic acid vectors. This review revisits relevant structural and mechanistic features of viruses as design considerations for efficient nucleic acid delivery systems. This article explores how viral ligand display and a metastable structure are central to the molecular mechanisms of attachment, entry, and viral genome release. For comparison, accounted for are details on the design and intracellular fate of existing nucleic acid carriers and nanostructures that share similar and essential features to viruses. The review, thus, highlights unifying themes of viruses and nucleic acid delivery systems such as genome protection, target specificity, and controlled release. Sophisticated viral mechanisms that are yet to be exploited in oligonucleotide delivery are also identified as they could further the development of next-generation nonviral nucleic acid vectors.